2018
DOI: 10.24953/turkjped.2018.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Chelation therapy for secondary neonatal iron over load: Lessons learned from rhesus hemolytic disease

Abstract: Secondary neonatal iron overload occurs with intrauterine and post-natal blood transfusions. Treatment with intravenous Deferoxamine was reported only in four cases in the literature. Herein we report a case of a patient born at 36 weeks of gestation, who had rhesus hemolytic disease. He developed secondary iron overload, causing liver injury, after a total of six blood transfusions: four intrauterine and 2 post-natal transfusion therapies. Intravenous Deferoxamine treatment was started at the age of 45 days d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…Historically, inspissated bile syndrome was suggested because of direct occlusion of the bile collecting system by the large flux of bilirubin in dehydrated bile resulting from the hemolysis. [5][6][7][8] More recently, direct-iron toxicity on the fetal or infant liver has been implicated, with liver biopsies revealing iron deposition in hepatocytes, 9,[13][14][15][16][17] as was observed in our second case. Several studies have revealed that infants with HDFN, even without liver disease, have high plasma ferritin levels suggestive of iron overload, which is worsened in patients who received IUT.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Historically, inspissated bile syndrome was suggested because of direct occlusion of the bile collecting system by the large flux of bilirubin in dehydrated bile resulting from the hemolysis. [5][6][7][8] More recently, direct-iron toxicity on the fetal or infant liver has been implicated, with liver biopsies revealing iron deposition in hepatocytes, 9,[13][14][15][16][17] as was observed in our second case. Several studies have revealed that infants with HDFN, even without liver disease, have high plasma ferritin levels suggestive of iron overload, which is worsened in patients who received IUT.…”
Section: Discussionmentioning
confidence: 53%
“…Retrospectively, our experience further supports judicious evaluation because both cases had HDFN-associated cholestasis, IUT, and varying degrees of hepatocellular injury that triggered broad evaluations (including liver biopsy) that were unrevealing for alternative diagnoses. Case 1 and others 9,13,16,17,21 highlight that extreme hyperferritinemia is consistent with HDFN-associated cholestasis; likewise, case 2 and others 18 indicate that liver transaminases even .1000 U/mL may also be part of this syndrome.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…DM mesylate stock (Fresenius Kabi) was dissolved in saline at 100 g/L. Doses were extrapolated from human chelation dosing for DM at 9 mL/kg body weight, 17,18 thus providing a total chelator concentration of 26 mmol/L (iron‐binding equivalents), 17,19–21 which was achieved by DM group receiving an intravascular infusion at a concentration of 0.6 mmol/L as adapted from published data 22–24 …”
Section: Methodsmentioning
confidence: 99%
“…DM mesylate stock (Fresenius Kabi) was dissolved in saline at 100 g/L. Doses were extrapolated from human chelation dosing for DM at 9 mL/kg body weight, 17,18 thus providing a total chelator concentration of 26 mmol/L (iron-binding equivalents), 17,[19][20][21]…”
Section: Dm Dosingmentioning
confidence: 99%